(untitled) (Acta Scientiarum. Biological Sciences, 2022)
The olive crop has a large diversity in cultivars around the world, whose identification have been based on leaf, stem or fruit traits. However, these traits may be influenced by the environment, which has led to the misidentification of cultivars. The variability of the pistil and pollen structure under electron scanning and light microscopy were studied using the cultivars ’Arbequina’, ’Arbosana’, ’Frantoio’, ’Koroneiki’, ’Manzanilla de Sevilla’ and ’Picual’, cultivated in Southern Brazil. The aim was to find unique patterns for their identification. This type of study has not been carried out in the conditions of Southern Brazil, where the identification of commercial cultivars sometimes is complex and confusing. There were significant differences in the variables, showing uniformity within each cultivar in different locations. The principal component analysis indicated a separation of cultivars according to similarities or micromorphological differences in the pollen wall, area of the lumen and the structural elements of the tectum. For the analysis of the pistil, the separation was even clearer, each cultivar individually forming a cluster, using as characters the length of the style in contrast to the length, width and area of the stigma. This evidenced little variation among individuals within the same cultivar. The information provided can contribute to the individual identification of very close olive tree cultivars in the conditions of Southern Brazil.